The stoichiometry of the electrogenic sodium bicarbonate cotransporter pNBC1 in mouse pancreatic duct cells is 2 HCO(3)(−):1 Na(+) - Gross, E (Blackwell Science Inc, 2001)
1. The electrogenic sodium bicarbonate cotransporter pNBC1 is believed to play a major role in the secretion of bicarbonate by pancreatic duct cells, by transporting bicarbonate into the cell across the basolateral membrane. Thermodynamics predict that this function can be achieved only if the reversal potential of the cotransporter is negative to the cell’s membrane potential, or equivalently that the HCO(3)(−):Na(+) stoichiometry is not larger then 2:1. However, there are no data available on either the reversal potential or the HCO(3)(−):Na(+) stoichiometry of pNBC1 in pancreatic cells. 2. We studied pNBC1 function in mouse pancreatic duct cells. RT-PCR analysis of total RNA revealed that these cells contain the message for pNBC1, but not for kNBC1, NBC2 or NBC3. 3. To measure cotransporter activity, mouse pancreatic duct cells were grown to confluence on a porous substrate, mounted in an Ussing chamber, and the apical plasma membrane permeabilized with amphotericin B. Ion flux through pNBC1 was achieved by applying Na(+) concentration gradients across the basolateral plasma membrane. The current through the cotransporter was isolated as the difference current due to the reversible inhibitor dinitrostilbene disulfonate (DNDS). 4. Current-voltage relationships for the cotransporter, measured at three different Na(+) concentration gradients, were linear over a range of about 100 mV. The reversal potential data, obtained from these current-voltage relationships, all corresponded to a 2 HCO(3)(−):1 Na(+) stoichiometry. 5. The data indicate that pNBC1 is functionally expressed in mouse pancreatic duct cells. The cotransporter operates with a 2 HCO(3)(−):1 Na(+) stoichiometry in these cells, and mediates the transport of bicarbonate into the cell across the basolateral membrane.